Dual band aperture couple microstrip patch antenna using elliptical aperture shape - Ahmed, Maher B.; S.K., A. Ranim; A. Al-Malsi, Abdulrahman; M.Z., M. Nor; Kamarudin, M. R. (2010)
A Wireless Local Area Network (WLAN) application nowadays has become more popular. Since it allows users to access network services without being attached to a wired infrastructure. Microstrip antenna has advantages that made them a perfect candidate for the wireless local area network (WLAN) applications. Nowadays, microwave frequencies in communication and radar applications were widely used and for that, certain antenna performance requirements are needed and should be an integral part of the design process. GPS (Global Positioning System), Wireless Local area network (WLAN) are the example of applications that share a common requirement in their antennas. They all require an antenna that is small in size and volume, low in cost and weight, easy to design, and can perform efficiently at two distinct frequencies that may be separated far apart. This paper describes on the design of dual band aperture coupled microstrip patch antenna using elliptical aperture shapes that operate at 2.4 GHz and 5.8 GHz These designs were simulated using Computer Simulation Technology (CST) software to gain simulation results and next, this antenna were tested with vector network analyzer. Both, simulated and measured data were compared.